Self Regulated Learning and Spiritual Practices Alleviate Educational Stress: Pembelajaran Regulasi Diri dan Praktik Spiritual Meredakan Stres Pendidikan - Yunita Najwa Salim; Wahidin Wahidin (Academia Open, 2026)
General Background Educational stress represents a prominent psychological challenge for university scholars facing rigorous institutional standards worldwide. Specific Background Within Indonesian religious higher education institutions, final-year cohorts experience compounded pressures from thesis requirements and specific institutional moral expectations. Knowledge Gap Despite existing literature on undergraduate tension, empirical investigations detailing how learners in religious pedagogical programs simultaneously apply cognitive, social, and introspective coping mechanisms remain scarce. Aims This study identifies the multidimensional manifestations of scholastic apprehension and the corresponding coping mechanisms utilized by the 2022 cohort at the Faculty of Tarbiyah and Teacher Training of UIN Salatiga. Results Phenomenological qualitative analysis of eight purposively selected participants revealed that physiological symptoms universally accompanied cognitive personal doubt and behavioral procrastination. To manage these pressures, participants simultaneously deployed cognitive planning, peer networks, and specific Islamic rituals such as prayer and introspection. Novelty This research distinctly maps the dual identity of religious education scholars who seamlessly integrate modern psychological self-regulation with traditional theological rituals to navigate final-year academic pressures. Implications University administrators must strengthen integrated counseling services that incorporate theological values to support psychological well-being and resolve structural support deficits in higher education environments. Highlights Final year undergraduates experienced severe physiological symptoms alongside cognitive personal doubt. Peer support networks significantly reduced the psychological burdens of thesis completion. Religious introspection combined with cognitive planning successfully mitigated behavioral procrastination. Keywords Self Regulated Learning; Islamic Spirituality; Educational Stress; Phenomenological Approach; Peer Support